Pengembangan Multimedia Interaktif Berbasis Articulate Storyline pada Pembelajaran Tematik Abad 21 bagi Siswa Sekolah Dasar - Itsnaaini Nur Halimah; Fitri Indriani (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2021)
The use of interactive multimedia in the 21st-century era in learning is necessary to enable students to develop various skills, especially 21st-century skills. This research aims to produce interactive multimedia products based on articulate storylines on the thematic understanding of the 21st century for elementary school students. This type of research is Research and Development with ADDIE (Analysis, Design, Development, Implementation, Evaluation) research model. A team of experts assess the product quality test: material experts, media experts, learning experts, and linguists, assessments from teachers, and student response questionnaires. The evaluation results have obtained as follows; Material expert assessment results in 90 (very good), media experts 90 (very good), learning experts 85 (very good), linguists (good), teacher ratings 95 (very good), and student response 84 (excellent). The average score of the evaluation results is 86.04, thus, the product can be declared worthy as a medium and support learning with the category "very good." Penggunaan multimedia interaktif di era abad 21 dalam pembelajaran sangatlah diperlukan dalam rangka mengaktifkan siswa serta mengembangkan berbagai keterampilan terutama keterampilan abad 21. Penelitian ini bertujuan menghasilkan produk multimedia interaktif berbasis articulate storyline pada pembelajaran tematik abad 21 bagi siswa sekolah dasar. Jenis penelitian ini adalah Research and Development dengan model penelitian ADDIE (Analysis, Design, Development, Implementation, Evaluation). Adapun uji kualitas produk dinilai oleh tim ahli yaitu; ahli materi, ahli media, ahli pembelajaran, dan ahli bahasa, penilaian dari guru dan angket respon siswa. Hasil penilaian diperoleh sebagai berikut; hasil penilaian ahli materi 90 (sangat baik), ahli media 90 (sangat baik), ahli pembelajaran 85 (sangat baik), ahli bahasa (baik), penilaian guru 95 (sangat baik), dan respon siswa 84 (sangat baik). Rata-rata hasil penilaian produk 86,04, sehingga produk dapat dinyatakan layak sebagai media dan penunjang belajar dengan kategori “sangat baik”.